Digital hearing-aid examination - Frye, George J. (Auditio, 2021)
There is a widespread notion among hearing-aid fitting professionals that the response of digital hearing aids cannot be examined. This idea is erroneous since we have the technology to carry out these studies. In this article, we present the necessary methodology for the examination of digital hearing aids using pure and composite tone signals. This methodology allows the interactive analysis of the response of the noise reduction filters characteristic of digital hearing aids. Thus, a review of the analysis of the responses is carried out through the use of spectography techniques. Translated with permission of the author by Franz Zenker. Original Article: Frye GJ. Testing Digital Hearing Instruments [en linea]. Hearing Review. 13 link